UPAYA PENINGKATAN KREATIVITAS DAN INOVASI UMKM DENGAN BUKU REFERENSI INSPIRATIF DI KOTA SERANG - Khaeruman, Khaeruman; Harsono, Pramudi; Tabroni, Tabroni; Suflani, Suflani; Bahits, Abdul; Salapudin, Salapudin; Sukmawan, Irwan; Komarudin, Mochamad Fahru; Lesmana, Ihwan Satria; Triana, Leni (Indonesian Collaboration Journal of Community Services (ICJCS), 2024)
The community service activity entitled "Efforts to Enhance Creativity and Innovation in MSMEs with Inspirational Reference Books in Serang City", held in September 2024, aimed to improve the creativity and innovation of MSME entrepreneurs. Through a webinar and book review of "Inspirational MSMEs: Secrets to Success in the Modern Era", participants gained valuable insights into product innovation, digital marketing strategies, and efficient financial management. The activity was successful in equipping MSME entrepreneurs with new knowledge and skills, motivating them to apply creative ideas and utilize digital media for business development. Feedback surveys revealed that participants felt more confident and prepared to face challenges and expand their businesses. Furthermore, the event fostered networking opportunities for MSME entrepreneurs, which could further support their business growth. Overall, this community service activity contributed positively to enhancing the competitiveness of MSMEs in Serang City and can serve as a model for similar initiatives in other regions